Emotional Availability of Low-income Mothers and Their Children: Association with Salivary Cortisol - Arias, Anel (CSULB McNair Scholars Program)
Negative interactions between mothers and their children have been shown to lead to several poor health outcomes in children, including increases in stress, depression, and disruptive behaviors (e.g., fussiness, crying spells). This study examines whether more positive mother-child interactions (i.e., sensitivity, structuring, non-intrusiveness, non-hostility, responsiveness, and involvement) are associated with lower physiological levels of stress (i.e., cortisol) at 2-4 years postpartum among low-income mothers and their children. Our sample consisted of 90 low-income mothers that had an annual income of less than $20,000. A modified version of the Emotional Availability Scales (EAS) for infancy and early childhood was used to rate mother-child interactions. To measure physiological levels of stress, our study examined cortisol levels by having mothers collect their saliva and their children's saliva at their homes. A multiple regression analysis found sensitivity, structuring, and responsiveness to be significantly associated with mothers' cortisol slope, after controlling for child age and child language (P<0.05). Involvement was found to be marginally significant with mothers' cortisol slope (P=0.06). No significant results were found for non-hostility, non-intrusiveness, average cortisol levels, and child cortisol slope. Identifying more positive mother-child interactions that reduce stress in early life will influence the teaching methods of stress management programs for low-income families.